Efficient Production of the Dicarboxylic Acid Glutarate by Corynebacterium glutamicum via a Novel Synthetic Pathway - Pérez-García, Fernando; Jorge, João M. P.; Dreyszas, Annika; Risse, Joe Max; Wendisch, Volker F. (Frontiers in Microbiology, 2018)
The dicarboxylic acid glutarate is an important building-block gaining in the chemical and pharmaceutical industry. Here, a synthetic pathway for fermentative production of glutarate by the actinobacterium Corynebacterium glutamicum has been developed. The pathway does not require molecular oxygen and operates via lysine decarboyxylase followed by two transamination and two NAD-dependent oxidation reactions. Using a genome-streamlined strain L-lysine producing strain as basis metabolic engineered was performed to enable conversion of L-lysine to glutarate in a five-step synthetic pathway comprising lysine decarboxylase, putrescine transaminase and γ-aminobutyraldehyde (GABA) dehydrogenase from E. coli and GABA/5AVA amino transferase and succinate/glutarate semialdehyde dehydrogenase either from C. glutamicum or from three Pseudomonas species. Loss of carbon via formation of the by-products cadaverine and N-acetylcadaverine was avoided by deletion of the respective acetylase and export genes. As the two transamination reactions in the synthetic glutarate biosynthesis pathway yield L-glutamate, biosynthesis of L-glutamate by glutamate dehydrogenase was expected to be obsolete and, indeed, deletion of its gene gdh increased glutarate titers by 10%. Glutarate production by the final strain was tested in bioreactors in order to investigate stability and reliability of the process. Efficient glutarate production from glucose was achieved by fed-batch fermentation with a volumetric productivity of 0.32 g L−1 h−1, an overall yield of 0.17 g g−1 and a titer of 25 g L-1.